A Review of Bhramari Pranayama’s Impact on Mental Health. - Yadav, Prem (International Research Journal of Ayurveda & Yoga, 2023)
Background -People’s lifestyles have become very mechanical in the modern day. Everyone is in a rat race to meet their goals, which causes stress. The repercussions of this stress on a person’s physical and mental health are further. The healthy development of emotional attitudes and personality that coexist peacefully with the entire society or community is what is meant by mental health. Sadvrittapalan, application of Acharrasayana, Yoga, and meditation practises are crucial for mental health prevention. Yoga consists of eight steps, and to control the sense organs called Indriyas, Pranayam is crucial. Significant and simple form of Ashtakumbhaka is Bhramari Pranayam. The humming sound of Bhramari Pranayam causes vibrations in the body that directly affect the hypothalamus of the brain, relieving tension and bringing about calmness and happiness throughout the body. In order to offer a better answer, this article discusses the function of Bhramari Pranayama in the prevention and promotion of mental health. Material & Methods:-The data used in the current investigation was gathered from primary and secondary sources, namely literature reviews of major Ayurvedic Samhitas and texts and widely disseminated research publications. Conclusions:-This study demonstrates the critical impact Bhramari Pranayama plays in both the prevention of mental illness and the treatment of mental diseases like stress, anxiety, and depression. Ayurveda claims that continuous practise of Bhramari Pranayama reduces the Raja and Tamadosha and increases Satvaguna, thereby aiding in the development of mental health.